ANALISA JARINGAN, POLA DAN BUDAYA KOMUNIKASI ORGANISASI DI PT ASTRA HONDA MOTOR (AHM), MAJALENGKA - Ramadhan, Fardhal Virgiawan; Anggraeni, Diana (UNIVERSITAS STEKOM, 2024)
Automotive developments in Indonesia have been proven to be able to advance the Indonesian economy. This is proven by the fact that this sector is able to contribute around Rp. 99.16 Trillion. PT Astra Honda Motor (AHM) is one of the companies operating in the automotive sector that is successful in this marketing. The success achieved will certainly be related to the network, patterns, and culture of organizational communication carried out. This is because, with the formation of networks, organizational communication patterns, and culture, cooperation will increase to achieve its goals. The aim of this research is to analyze the network, patterns, and culture of organizational communication at PT Astra Motor Honda (AHM) Majalengka. The research method used is qualitative with primary and secondary data collection techniques, by conducting a Focus Group Discussion (FGD) to interpret the findings obtained. The results of this research show that AHM Majalengka has an organizational communication network and pattern, which can be seen in the communication network having several characteristics such as opinion leaders, bridges, and gatekeepers. The Organizational Communication Pattern has 2 (two) patterns, namely the Chain Communication Pattern which is found from the Main Director to the Director to the HRD Manager, while the Y Organizational Communication Pattern is found in the HRD Manager to several divisions such as Psychologist, Marketing, Account & ADM Manager, Operational Division, and Recruitment Division.